2018
DOI: 10.1080/15376516.2018.1506849
|View full text |Cite
|
Sign up to set email alerts
|

Syzygium AromaticumAlleviates Cerium Chloride-Induced Neurotoxic Effect In The Adult Mice

Abstract: Previous studies have brought to light the toxic effect of cerium chloride (CeCl) but very little is known about the oxidative brain injury caused by this metal. Medical plants have a well-recognized role in the management of damage caused by pollutants such as CeCl. Syzygium aromaticum, a potent natural source of bioactive compounds and rich in secondary metabolites, has a broad range of biological functions. The aim of this study is to investigate the capacity of Syzygium aromaticum ethanol extract (ESA) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Studies have been showed that ESA has been used as antibiotic in the treatment of scabies, cholera, malaria, and tuberculosis (Cortés‐Rojas et al, 2014). It is harnessed used for the treatment of various ailments including cardiovascular defects, tumor, and psychological disorders (Bhowmik et al, 2012; El‐Saber Batiha et al, 2020; Kadri et al, 2019). It can also penetrate the blood–brain barrier and play an effective antioxidant function in the CNS (Cortés‐Rojas et al, 2014; El‐Saber Batiha et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have been showed that ESA has been used as antibiotic in the treatment of scabies, cholera, malaria, and tuberculosis (Cortés‐Rojas et al, 2014). It is harnessed used for the treatment of various ailments including cardiovascular defects, tumor, and psychological disorders (Bhowmik et al, 2012; El‐Saber Batiha et al, 2020; Kadri et al, 2019). It can also penetrate the blood–brain barrier and play an effective antioxidant function in the CNS (Cortés‐Rojas et al, 2014; El‐Saber Batiha et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Thus the obtained dried extracts were stored at 4 °C in labeled and stored in sterile bottles (Engida et al, 2013). The dose of Syzygium aromaticum was chosen in accordance with Kadri et al (2019).…”
Section: Methodsmentioning
confidence: 99%
“…Further fractionation revealed that polar bioactive constituents (tannins and polyphenols) were accountable for the enzyme inhibition. It is noteworthy that the ethanol bud extract from S. aromaticum corrected the AchE rate in cerium chloride (CeCl 3 )-induced memory-impaired mice [ 42 ]. This study revealed a clear association between memory and AchE activity, where improved cholinergic neural transmission alleviated the state of memory in mice.…”
Section: Neuroprotective Agents From Syzygiummentioning
confidence: 99%
“…They not only scavenge free radicals but also provide protective effects against other toxicities. For example, CeCl 3 -induced neurotoxicity in the brains of rats was improved by the antioxidant capacity of S. aromaticum to restore RIS levels, which alleviated the cholinergic neural transmission and the state of memory in mice [ 42 ]. In another study, the ability of antioxidants to maintain genomic stability and slow down aging was demonstrated in the Caenorhabditis elegans nematode model [ 85 ].…”
Section: Neuroprotective Agents From Syzygiummentioning
confidence: 99%
See 1 more Smart Citation